2020
DOI: 10.1016/j.jmst.2019.07.046
|View full text |Cite
|
Sign up to set email alerts
|

How does anodization time affect morphological and photocatalytic properties of iron oxide nanostructures?

Abstract: Iron oxide nanostructures are promising materials to be used as photocatalysts in different photoelectrochemical applications. There are different techniques in order to synthesize these nanostructures, but one of the most inexpensive and simple method is electrochemical anodization. This method can lead to different nanostructures by controlling its parameters. Anodization time is one of the most critical parameters since it considerably affects the properties of the obtained nanostructures. In this work, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The slope of the M–S plots is inversely related to the donor density of semiconductor materials. 69 It is evident from the M–S plots, as shown in Fig. 10A, that the slope progressively decreased in the case of both the CuO and ZnO series, with the lowest slopes observed for CuO-5 and ZnO-5, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…The slope of the M–S plots is inversely related to the donor density of semiconductor materials. 69 It is evident from the M–S plots, as shown in Fig. 10A, that the slope progressively decreased in the case of both the CuO and ZnO series, with the lowest slopes observed for CuO-5 and ZnO-5, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…They found that annealed nanoporous Fe 2 O 3 films exhibited a net photocurrent density of 0.51 mA cm -2 at 0.6 V vs. Ag/AgCl in an electrolyte containing 0.5 mol L -1 H 2 O 2 and 1 mol L -1 NaOH under AM 1.5 simulated solar illumination. Since then, many studies have featured the PEC properties of nanostructured iron oxide films fabricated by anodization [31][32][33][34][35][37][38][39][40][42][43][44]49,52,53,[56][57][58]67,[72][73][74][75] . The Misra group demonstrated that a photoanode with a two-layer oxide structure comprising a top layer with a nanodendrite morphology and a bottom layer with a nanoporous morphology, obtained by the two-step anodization of Fe, exhibited noticeably improved photoactivity compared to that of a single layer nanotubular oxide [33,34] .…”
Section: Pec Applicationsmentioning
confidence: 99%
“…In addition to their very promising applications in PEC water splitting, anodic iron oxide nanotube arrays have also shown good photocatalytic performance in the degradation of methylene blue under visible light [42,52] and excellent oxygen reduction reaction catalytic activity [55] . In addition, Joseph et al reported the synthesis of metal-doped iron oxide nanoporous structures achieved by an additional simple electrochemical process after Fe anodization [57,77] . The metal-doped iron oxide nanostructures exhibited enhanced photocatalytic activity.…”
Section: Pec Applicationsmentioning
confidence: 99%